Multimodal Discursive Construction of Inclusive Education by the Two Most Voted Presidential Candidates in the Chilean Elections of 2017 - Baeza Duffy, Patricia; Vásquez-Rocca, Liliana; Manghi H., Dominique (Íkala, Revista de Lenguaje y Cultura, 2020)
This paper aims to characterize the discursive construction of two Chilean presidential candidates of 2017 on education, from an intersubjective, multimodal and critical perspective, which integrates the multimodal discourse analysis, the appraisal model, and the critical discourse studies. The methodology is qualitative. The corpus is made up of the programs and television networks of the two Chilean presidential candidates. The analysis was developed in two stages, one descriptive and the other interpretive-integrative. After the analysis, the results showed that the construction of meanings is carried out through intersemiotic evaluative prosodies, in which predominate appreciations, and to a lesser extent, judgments and affects. These evaluative prosodies shape strategies of legitimization and delegitimization: discredit and concealment in Piñera and alignment in Guillier. In this way, Piñera perpetuates the status quo of market logic in education, while Guillier uses the macro-strategy of transforming that status quo. The use of perpetuation macrostrategies by Piñera, has had profound social implications in Chilean society since the discursive construction of the aforementioned politician responds to a neoliberal model that is characterized by the application of the principles that come from private companies that enter in tension with inclusive education as they encourage selection and segregation rather than inclusion.